Efektifitas Pestisida Biologis Bacillus Cereus dan Bacillus Megaterium. sebagai Pengendali Spodoptera litura Fabr (Lepidoptera: Noctuidae) - I Made Indra Agastya; Aminudin Afandhi; Luqman Qurata Aini (Jurnal Penelitian Pertanian Terapan, 2017)
This research was conducted in vitro in the laboratory. Studies conducted in the Laboratory of Bacteriology Department of Plant Pests and Diseases of the Faculty of Agriculture, University of Brawijaya, on the effectiveness of the bacteria Bacillus cereus and Bacillus megaterium as biological pesticides controlling Spodoptera litura. The objective of this study was to determine the effectiveness of the bacteria Bacillus sp as biological control. Effectiveness pesticide was measured by testing the incubation period and mortality in larvae of S. litura instar 3. This study used a completely randomized design (CRD), conducted observations every 6 hours until the larvae dead. The results showed that the percentage of mortality of S. litura reached 94.66% compared to the control, while the incubation time of the bacteria B. cereus cause disease until 29.84 hours. B. cereus and B. megaterium have the ability to incubate third instar larvae of S. litura up to 29.84 hours and caused the death of larvae up to 94.66%. Keywords: Biological pesticides, Bacillus cereus, Bacillus megaterium, entomopatogen, Spodoptera litura